Company Law: a historical evolution - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha; Ian Lilienthal, Gary; Jai Devaraj, Subash; Ahmad, Muhamad Hassan (Sweet & Maxwell, Thomson Reuters, 2025)
The evolution of corporate law in England and thereafter in Malaysia, from its colonial origins through independence and its current status forms the discussion of this chapter. Through analysis of historical records, legislative developments, and contemporary sources, the chapter examines how the corporate law has transformed from a transplanted colonial framework into a modern, sophisticated system adapted to local conditions and global business requirements. The development of Malaysian corporate law represents a unique case study in legal evolution, demonstrating the journey from colonial legal transplantation to indigenous adaptation. This transformation reflects broader patterns of economic development, political change, and social evolution in Malaysia’s transition from a colonial territory to a modern industrial nation. The key transitional periods, reform initiatives, and the ongoing challenges of balancing international standards with local business practices are highlighted.